The Evolution and Indigenization of Catholic Church Music among the Yoruba People of Southwestern Nigeria - Oyadiran, Kolawole Emmanuel (2015)
The purpose of this study was to explore the genesis and development of Church music; investigate the factors that occasioned the Second Vatican reforms vis-a-vis the Catholic Church music, and analyze the musical forms resulting from the Vatican II reforms. It further evaluated the impact of indigenization and the factors that influenced the musical forms resulting from Vatican II.